Shades of grey - domestic and sexual violence against women: law reform and society - Carline, Anna (A GlassHouse book, 2014)
"Adopting an explicitly feminist perspective, the book argues that law must be looked at holistically, and will investigate how the legal responses presuppose, maintain and perpetuate a certain context that may in fact not reflect women's experiences. Examples of law reform in the area of violence against women and its implementation will illustrate both the overt and the 'hidden gender' of so-called neutral or objective legal principles and structures. Drawing upon a range of material primarily from Australia and England/Wales but also from the US, Canada and European countries, the book highlights the indeterminacy of the legislation and how that translates into decision-making. Consequently, Carline and Easteal analyse the application and efficacy of the law. Through contextualizing and critiquing relevant legislation, case law, and studies into the legal system, as well as comparing violence against women and policy responses, Shades of Grey will assist law-makers, academics, policy-makers and a wider audience in understanding the complexities of violence against women and the potential and the limits of law. The book does even more though; both explicitly and implicitly it provides suggestions for best practice models for policy-making and law reform. It is intended that the book will help to improve the government, community and legal responses to women who experience violence. Contextual and comparative information is an invaluable source of the knowledge and ideas needed to deal more effectively with this global public health and human rights issue"--